Drug-Carrying Magnetic Nanocomposite Particles for Potential Drug Delivery Systems. (28th October 2009) - Asmatulu, R.; Fakhari, A.; Wamocha, H. L.; Chu, H. Y.; Chen, Y. Y.; Eltabey, M. M.; Hamdeh, H. H.; Ho, J. C.
Abstract : Drug-carrying magnetic nanocomposite spheres were synthesized using magnetite nanoparticles and poly (D, L-lactide-co-glycolide) (PLGA) for the purpose of magnetic targeted drug delivery. Magnetic nanoparticles (∼ 13 nm on average) of magnetite were prepared by a chemical coprecipitation of ferric and ferrous chloride salts in the presence of a strong basic solution (ammonium hydroxide). An oil-in-oil emulsion/solvent evaporation technique was conducted at 7000 rpm and 1.5–2 hours agitation for the synthesis of nanocomposite spheres. Specifically, PLGA and drug were first dissolved in acetonitrile (oily phase I) and combined with magnetic nanoparticles, then added dropwise into viscous paraffin oil combined with Span 80 (oily phase II). With different contents (0%, 10%, 20%, and 25%) of magnetite, the nanocomposite spheres were evaluated in terms of particle size, morphology, and magnetic properties by using dynamic laser light scattering (DLLS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and a superconducting quantum interference device (SQUID). The results indicate that nanocomposite spheres (200 nm to 1.1 μ m in diameter) are superparamagnetic above the blocking temperature near 40 K and their magnetization saturates above 5 000 Oe at room temperature.